(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2007)
Skinner’s analysis of verbal behavior requires understanding its experimental and philosophical underpinnings. His interpretation of the social behavior known as “language” builds directly from the experimental analysis of behavior in direct contact with its immediate milieu, both inner and outer, and from the framing of behavioral contact as contingency relations. The analysis of the contingency relations of verbal behavior, however, deals with properties of behavior not only under the dynamic controls of direct contact, but as that control is mediated by society. A social community constructs that mediation by shaping its members’ actions to teach other members how to verbalize effectively through the proper forms of action. As such, Skinner’s attributes of verbal behavior are: 1) relational; 2) mediational; 3) communal; and 4; stipulational. All four are necessary components of his analysis of verbal behavior, and constitute what he defines as verbal behavior.